2019
DOI: 10.1002/mc.23064
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Wnt signaling promotes olaparib resistant ovarian cancer

Abstract: Epithelial ovarian cancer (EOC) has one of the highest death to incidence ratios among all cancers. High grade serous ovarian carcinoma (HGSOC) is the most common and deadliest EOC histotype due to the lack of therapeutic options following debulking surgery and platinum/taxane‐based chemotherapies. For recurrent chemosensitive HGSOC, poly(ADP)‐ribose polymerase inhibitors (PARPi; olaparib, rucaparib, or niraparib) represent an emerging treatment strategy. While PARPi are most effective in homologous recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 80 publications
(84 citation statements)
references
References 47 publications
1
77
1
Order By: Relevance
“…Other studies have also suggested Wnt signaling drives enhanced DNA repair. Sun et al identified WNT16B as a driver of resistance to cytotoxic chemotherapy in prostate cancer (66) while Yamamoto et al identified WNT3A expression as the cause of in vitro olaparib resistance in an ovarian cancer cell (67). Here we find that Wnts regulate the expression of HR and FA pathway genes in part via a β-catenin/MYBL2 axis.…”
Section: Discussionmentioning
confidence: 48%
“…Other studies have also suggested Wnt signaling drives enhanced DNA repair. Sun et al identified WNT16B as a driver of resistance to cytotoxic chemotherapy in prostate cancer (66) while Yamamoto et al identified WNT3A expression as the cause of in vitro olaparib resistance in an ovarian cancer cell (67). Here we find that Wnts regulate the expression of HR and FA pathway genes in part via a β-catenin/MYBL2 axis.…”
Section: Discussionmentioning
confidence: 48%
“…Supporting these results, in non-small cell lung cancer it has been shown that maintaining the lung cancer stem cell population requires the degradation of the WNT negative regulators, increasing β-catenin mediated WNT activity (77). Furthermore, WNT signaling plays a critical role in the maintenance and propagation of ovarian cancer stem cells (78); it is critical in desmoid tumor formation (79), and in head and neck squamous carcinomas (HNSCC), where researchers have shown CSC elimination after WNT/β-catenin signaling was downregulated.…”
Section: Wnt Signaling Activation In Healthy Immune Response and In Tmentioning
confidence: 76%
“…Although this protective effect has been attributed to the downstream effectors of Wnt/b-catenin signaling such as survivin in one study, more generally the underlining mechanism still remains unclear (Watson et al, 2010;Gao et al, 2013;Nagano et al, 2013;Emons et al, 2017). Two recent studies found that elevated Wnt signaling enhanced the DNA damage repair and thereby conferred resistance to the PARP inhibitor olaparib in ovarian cancers (Fukumoto et al, 2019;Yamamoto et al, 2019). This mechanism could also protect cancer cells from DNA damage caused by other conventional chemo agents or radiation.…”
Section: Wnt Signaling Mediated Resistance In Cancer Therapymentioning
confidence: 99%
“…Wnt/b-catenin signaling mediated resistance to PARP inhibition in ovarian cancer due in part to upregulation of DNA damage repair. Inhibition of b-catenin signaling reverted resistance to olaparib in ovarian cancer xenografts (Fukumoto et al, 2019;Yamamoto et al, 2019). Vismodegib (Hedgehog signaling inhibitor)…”
Section: Resistance To Wnt Pathway Blockade In Normalmentioning
confidence: 99%